KECERDASAN VISUAL SPASIAL SISWA DITINJAU DARI TIPE KEPRIBADIAN HIPPOCRATES-GALENUS - Nur Hamidah; Susanto Susanto; Erfan Yudianto (Jurusan Pendidikan MIPA FKIP Universitas Jember, 2018)
Abstract: This research will describe students’ visual-spatial intelligence in terms of personality. There are four personality types, they are sanguine, choleric, melancholy, and phlegmatic. The subjects of this research are students of class X BIC 1 and X BIC 2 in MAN 1 Jember. The methods used in this research are test and interview. There are 5 subjects in this study, they are 1 sanguine, 1 choleric, 2 melancholy and 1 phlegmatic. This research uses descriptive design with qualitative approach. The result of this research shows that students’ visual-spatial intelligence consists of imagination, conceptualization, problem solving and pattern-seeking which range from level 1 to level 5. Melancholy students tend to be creative in solving two-dimensional figures problems. Keywords:Visual-spatial intelligence, personality type, melancholy.